Ocorrência de Escherichia coli O157:H7 e O26 sorbitol negativas em matadouro frigorífico de bovino e suscetibilidade a antimicrobianos - Nespolo, Natália Maramarque; Saba, Rachel Zoccal; Rossatelli, Dalila Aparecida; Fairbrother, John Morris; Rossi Júnior, Oswaldo Durival (Instituto Biológico, 2014)
Cattle beef could be a way of transmitting Escherichia coli O157: H7 and non-O157 to humans if they consume undercooked meat, being responsible for causing severe diseases such as hemolytic uremic syndrome. Bacterial resistance has become worrying concerning the efficacy in the treatment of diseases, and because of these aspects, the objective of this study was to verify the occurrence of E. coli O157: H7 and non-O157 in the stages of cattle slaughter and to evaluate the susceptibility of these bacteria against antimicrobial action. We collected from a cattle slaughterhouse 21 samples from manipulators' hands, 21 from knives and 300 from 50 animals in six points of the flowchart. The isolation was performed using the CT-SMAC agar and characterization of serotypes by PCR. There was higher occurrence of E. coli O157: H7 (12.0%) in animals and lower prevalence of E. coli O26 (8.0%) and O113 (2.0%). E. coli O26 was present in 9.52% of the knives. The presence of E. coli non-O157 sorbitol negative was an unexpected fact due to the method of isolation. All E. coli O157: H7 isolates were sensitive to tetracycline, cefepime, cefoxitin, ciprofloxacin and sulphazotrim, and 78.85% of them were resistant to cephalothin and 34.61% to ampicillin. All E. coli O26 were sensitive to cefepime, cefoxitin and sulphazotrim, and 88.23% were resistant to tetracycline and cephalothin and 82.35% to ampicillin. The antimicrobial multiresistance was observed in both serotypes. It should be, therefore, a criteria for using antimicrobial in treatments to avoid become a public health concern.

A carne bovina pode ser um meio de transmissão de Escherichia coli O157:H7 e de não-O157 para os humanos, que a ingerem mal cozida, sendo responsáveis por causarem doenças severas, como a síndrome hemolítico urêmica. A resistência bacteriana se tornou preocupante em relação à eficácia nos tratamentos das doenças, e tendo em vista tais aspectos este estudo teve os objetivos de verificar a ocorrência de E. coli O157:H7 e não-O157 em etapas do abate bovino, asssim como de avaliar a suscetibilidade dessas bactérias frente à ação de antimicrobianos. Foram colhidas em abatedouro bovino 21 amostras de superfície de mãos dos manipuladores, 21 de facas e 300 provenientes de 50 animais em seis pontos no fluxograma de abate. O isolamento foi realizado utilizando o ágar CT-SMAC e a caracterização dos sorotipos pela PCR. Houve uma ocorrência maior de E. coli O157:H7 (12,0%) nos animais, e menor ocorrência de E. coli O26 (8,0%) e de O113 (2,0%). E. coli O26 esteve presente em 9,52% das facas. A presença de E. coli não-O157 sorbitol negativa foi um fato inesperado devido ao método de isolamento utilizado. Todos os isolados de E. coli O157:H7 mostraram-se sensíveis à tetraciclina, cefepime, cefoxitina, ciprofloxacina e sulfazotrim, e 78,85% deles foram resistentes à cefalotina e 34,61% à ampicilina. Todas E. coli O26 foram sensíveis ao cefepime, cefoxitina e sulfazotrim, e 88,23% resistentes à tetraciclina e cefalotina e 82,35% à ampicilina. A multirresistência aos antibimicrobianos foi observada em todos os sorotipos, devendo, portanto, haver critérios no uso de antimicrobianos nos tratamentos para não se tornar um problema de saúde pública.
Occurrence of Escherichia coli O157:H7 and O26 sorbitol negative in a cattle slaughterhouse and susceptibility to antimicrobials
Keywords: Escherichia coli; matadouro frigorífico de bovino; antimicrobianos; Escherichia coli; cattle slaughterhouse; antimicrobial